2015
DOI: 10.1002/chem.201406570
|View full text |Cite
|
Sign up to set email alerts
|

Smart Soft‐Templating Synthesis of Hollow Mesoporous Bioactive Glass Spheres

Abstract: Hollow bioactive glass spheres with mesoporous shells were prepared by using dual soft templates, a diblock co-polymer poly(styrene-b-acrylic acid) (PS-b-PAA) and a cationic surfactant cetyltrimethylammonium bromide (CTAB). Hollow mesoporous bioactive glass (HMBG) spheres comprise the large hollow interior with vertical mesochannels in shell, which realize large uptake of drugs and their sustained release. The formation of hydroxyapatite layer on the surface of HMBG particles shows the clear evidence for promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 54 publications
4
26
0
Order By: Relevance
“…Another dual soft-template system comprising a polystyrene-b-poly(acrylic acid) (PS-b-PAA) diblock copolymer and a CTAB cationic surfactant can be also employed to synthesize hollow mesoporous bioglass spheres (HMBG). 136 Several PS-b-PAA micelles aggregate together through electrostatic interactions with positively-charged CTAB to form PS-b-PAA/CTAB composites with the inorganic source. PS-b-PAA polymeric micelles contribute to the formation of the hollow interiors, while CTAB forms vertical mesochannels in the shell.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…Another dual soft-template system comprising a polystyrene-b-poly(acrylic acid) (PS-b-PAA) diblock copolymer and a CTAB cationic surfactant can be also employed to synthesize hollow mesoporous bioglass spheres (HMBG). 136 Several PS-b-PAA micelles aggregate together through electrostatic interactions with positively-charged CTAB to form PS-b-PAA/CTAB composites with the inorganic source. PS-b-PAA polymeric micelles contribute to the formation of the hollow interiors, while CTAB forms vertical mesochannels in the shell.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…The principle is that a sol-gel-like reaction will take place in droplets formed by surfactants. Using poly(styrene- b -acrylic acid) and CTAB, Li et al have obtained monodispersed 250 nm hollowed particles [32]. With a similar protocol, but using ethyl acetate along with CTAB, Liang et al also obtained mesoporous well-defined particles, with a size ranging from 133 to 254 nm depending on the ammonia concentration used [33].…”
Section: Synthesis Of Bioactive Glass Nanoparticlesmentioning
confidence: 99%
“…More interestingly, they showed that a solvothermal treatment induced the formation of pineal nanoparticles with a lamellar mesostructure, particles with an aspect ratio depending on the ammoniac concentration [33]. Hollow 250 nm particles with 20 nm pores inside the core and a vertical mesostructured 50 nm-thick shell have been synthesized using a dual soft template route using poly(styrene- b -acrylic acid) and CTAB [32]. This study distinguishes itself from the previously cited ones on the analysis of a cancer drug (doxorubicin) load and release.…”
Section: Materials Design For Biomedical Applicationsmentioning
confidence: 99%
“…Other surfactants that were also noted including dodecylamine and Triton X‐100 with n ‐hexanol . Table summarizes the various surfactants and concentration used in previous studies for synthesis as well as the characteristics of fabricated MBGs …”
Section: Use Of Surfactants In Mbg Synthesismentioning
confidence: 99%